Anatomic Total Shoulder Arthroplasty Using a Self-Pressurizing Pegged Bone-Preserving Cemented Glenoid Component: A 2- to 5-Year Follow-up Study. (January 2018) - Sanchez-Sotelo, Joaquin; Nguyen, Ngoc Tram V; Morrey, Mark
Background: High rates of radiographic loosening have been reported with various glenoid designs. Many available designs sacrifice most of the bone at the central portion of the glenoid vault, creating large areas of deficiency when revision becomes necessary. The purpose of this study was to report the 2- to 5-year outcome of shoulder arthroplasty using a bone-preserving all-polyethylene glenoid components with self-pressurizing pegs. Methods: Between August 2011 and December 2014, 202 consecutive anatomic total shoulder arthroplasties (TSAs) were performed by a single surgeon with implantation of a self-pressurizing cemented pegged glenoid component in 190 patients (12 patients had both shoulders replaced). Patients were followed up prospectively and evaluated for pain, motion, strength, American Shoulder and Elbow Surgeons (ASES) scores, and radiographic changes. The mean follow-up time was 2.7 (2–5) years. Results: TSA improved pain and function reliably. At the most recent follow-up, 94% of the shoulders had no or mild pain. Motion included 154 ± 25° of elevation, 68 ± 18° of external rotation, and median internal rotation to T10 (range, iliac crest to T4). The most recent average ASES score was 82 ± 15 points. Early postoperative radiographs showed no radiolucent lines. No humeral or glenoid component was considered radiographically loose at the most recent follow-up. Complications requiring reoperation included subscapularis insufficiency (4), posterior instability (2), deep infection (1), stiffness (1), and a painful loose body (1). No components were revised for loosening. Conclusions: Anatomic TSA using a cemented bone-preserving all-polyethylene pegged self-pressurizing glenoid component provided satisfactory clinical outcomes and survival at 2 to 5 years.